1998
DOI: 10.1093/hmg/7.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel gene for familial febrile convulsions, FEB2, linked to chromosome 19p in an extended family from the Midwest

Abstract: Febrile convulsions are a common form of childhood seizure. It is estimated that between 2 and 5% of children will have a febrile convulsion before the age of 5. It has long been recognized that there is a significant genetic component for susceptibility to this type of seizure. Wallace, Berkovic and co-workers recently reported linkage of a putative autosomal dominant febrile convulsion gene to chromosome 8q13-21. We report here another autosomal dominant febrile convulsion locus on chromosome 19p. Linkage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 22 publications
0
87
0
3
Order By: Relevance
“…Our review of the literature found that three loci, FEB1 on 8q (29), FEB2 on 19p (30), and FEB4 on 5q (31), were reported to be related to FSs with an autosomal dominant pattern of inheritance. Additionally, a mutation in the GABRG2 gene has been identified in individuals with FSs either with or without childhood absence epilepsy (7).…”
Section: Discussionmentioning
confidence: 98%
“…Our review of the literature found that three loci, FEB1 on 8q (29), FEB2 on 19p (30), and FEB4 on 5q (31), were reported to be related to FSs with an autosomal dominant pattern of inheritance. Additionally, a mutation in the GABRG2 gene has been identified in individuals with FSs either with or without childhood absence epilepsy (7).…”
Section: Discussionmentioning
confidence: 98%
“…The human recessive disorder Cayman ataxia [ATCAY (Nystuen et al 1996)] has been located proximal to D19S424. Similarly, a form of febrile seizures (FEB2) has been mapped to 19p13.3 proximal to D19S591 and distal to D19S395 (Johnson et al 1998). Thus, the mouse homolog of ATCAY or FEB2 could be expected either on mouse chromosome 10 within the inversion, outside of the inversion on the proximal end, or on mouse chromosome 17.…”
Section: Relevance For Mapping Disease Genesmentioning
confidence: 99%
“…comm.). Interestingly, two human loci, Cayman ataxia, ATCAY (Nystuen et al 1996) and a form of infantile febrile seizures, FEB2 (Johnson et al 1998), are disorders whose symptoms overlap with the phenotypes of the jittery, hesitant, and apathetic mouse mutants. A careful comparative map will be useful in determining whether any of these mouse mutants are homologous to any of the human disorders.…”
mentioning
confidence: 99%
“…4,15 In addition, linkage studies have identified 7 genomic regions likely to harbor genes increasing risk for GEFSϩ and 5 regions likely to harbor genes increasing risk for FS (table 1). [16][17][18][19][20][21][22][23][24][25][26] Two loci originally described as FS loci (FEB3 and FEB4) were reported in pedigrees best classified as GEFSϩ due to phenotypes beyond typical FS. 20,21,27 Here we describe a GEFSϩ kindred from Central America with evidence for linkage to chromosome 6q16.…”
mentioning
confidence: 99%